TRANSFORMATIONAL LEADERSHIP DALAM MANAGEMENT REVIEW SUB DIREKTORAT AIRCRAFT SERVICES PT DIRGANTARA INDONESIA - Riza Fathoni Ishak; Silma Kafah Dinilah; Deden Syarifudin; Elin Herlina (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
The role of top management at PT. Indonesian Aerospace plays an important role in an organizational system that has accountability according to the AS9110C standard in ISO 9001: 2015 placing special emphasis on leadership. The role of Top Management in the Aircraft Services Sub-Directorate is considered not to be fully integrated. This can be seen from the Management Review implementation process which has not been properly monitored, still leaving 56% of the target subjects unattained by the end of 2021. The objective in this article is to identify and analyze the involvement and role of the Top Management Sub Directorate of Aircraft Services in the process of implementing and achieving the Management Review targets. The approach method used is descriptive-qualitative using statistical analysis and the PCDA Circle method. The results of the study show that the role of Top Management in management involvement and management is considered to be lacking. This is shown through the Implementation Leadership Scale (ILS) which is still at 2.61 on a scale of 4. To improve this, an evaluation of the operational process is required through the PDCA cycle as one of the leadership tools in accordance with the AS9110C standard. The Aircraft Services Sub-Directorate can apply transformational leadership in accordance with the theory of the Full-Range Leadership Model through an integrated Management Review process by implementing the Management Review Integrated System. This research contributes to the implementation of strategic management between leadership and involvement in the company's management process